An Internal Fractional Boundary Placement Model for the Transmission-Line Modeling Method - Panitz, Mark; Christopoulos, Christos (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper describes a fractional boundary placement model for the transmissionline modeling method enabling the positioning of internal boundaries at non-integer cell locations. The model does not introduce any restriction on the maximum timestep of simulations. The connection of the boundary model to a regular mesh is shown and the model is validated using a band-pass waveguide filter model. Results show good agreement with the analytical solution for the waveguide problem.